Active Ageing across the Life Course: Towards a Comprehensive Approach to Prevention. (3rd February 2021) - Foster, Liam; Walker, Alan
Abstract : "Active ageing" has become the leading scientific and policy conceptualization of a later life over the past two decades in the European Union (EU). It has been used as a key strategy for responding to demographic ageing. In the United States, in contrast, discourses around successful ageing have been more prevalent. This review article charts the development of active ageing responses to demographic change, showing how the concept compares with the notion of successful ageing and other terms associated with "ageing well." It identifies how, in practice, active ageing has been dominated by a narrow economic or productivist interpretation that prioritizes the extension of working life (to reduce the "burden" of population ageing). Such interpretations of active ageing undermine its value and emphasize the need for a more comprehensive approach which is set out. The development of the Active Ageing Index in 2012 provided a new analytical tool to promote evidence-based strategies towards population ageing. However, in practice, we show how it has not yet engaged fully with a comprehensive approach to active ageing or with the critical role of the life course in shaping the experience of old age. Nonetheless, this review article shows that the concept of active ageing still has an important role to play in our understanding of and responses to population ageing.